The Effects of RF Sputtering Power and Gas Pressure on Structural and Electrical Properties of ITiO Thin Film - Accarat Chaoumead; Youl-moon Sung; Dong-Joo Kwak (Advances in Condensed Matter Physics)
Transparent conductive titanium-doped indium oxide (ITiO) films were deposited on corning glass substrates by RF magnetron sputtering method. The effects of RF sputtering power and Ar gas pressure on the structural and electrical properties of the films were investigated experimentally, using a 2.5 wt% TiO2-doped In2O3 target. The deposition rate was in the range of around 20~60 nm/min under the experimental conditions of 5~20 mTorr of gas pressure and 220~350 W of RF power. The lowest volume resistivity of 1.2×10−4  Ω-cm and the average optical transmittance of 75% were obtained for the ITiO film, prepared at RF power of 300 W and Ar gas pressure of 15 mTorr. This volume resistivity of 1.2×10−4  Ω-cm is low enough as a transparent conducting layer in various electrooptical devices, and it is comparable with that of ITO or ZnO:Al conducting layer.